THE EFFECT OF THE CONIFEROUS ENERGY ADDITIVE ON THE METABOLISM AND THE QUANTITATIVE AND QUALITATIVE INDICATORS OF DAIRY COWS' PRODUCTIVITY - Prytkov, Yuriy; Kistina, Anna; Dorozhkina, Ekaterina; Ruin, Vadim (Revista Inclusiones, 2020)
The article presents the results of studying the effect of the coniferous energy additive on the qualitative and quantitative indicators of milk productivity. It has been found that the introduction of the coniferous energy additive in the dosage of 17 g/kg of the dry matter to the cows' diet contributed to increasing the milk productivity and the biological value of the milk.